2021
DOI: 10.1101/2021.10.13.21264894
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Memory B cell and humoral responses elicited by Sputnik V in naïve and COVID-19-recovered vaccine recipients

Abstract: The development of effective vaccines against SARS-CoV-2 remains a global health priority. Despite extensive use, the effects of Sputnik V on B cell immunity need to be explored in detail. We show that B memory cell (MBC) and antibody responses to Sputnik V were heavily dependent on whether the vaccinee had a history of SARS-CoV-2 infection or not. In vitro stimulated MBCs from previously infected recipients of Sputnik V secreted a significant amount of anti-RBD IgG both on days 28 and 85 from the beginning of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…It has even been reported that a single dose of Sputnik V can significantly increase the antibody level in vaccine recipients without a history of COVID-19 (10). Also, the induction of memory B cell responses in Sputnik V was promising (12). Regardless of the high efficacy of the Sputnik V against the wild-type SARS-CoV-2 and the alpha variant (VOC 1, B.1.1.7), there are some concerns about the efficacy of the vaccine in dealing with the emerged variants, such as beta or B.…”
Section: Discussionmentioning
confidence: 99%
“…It has even been reported that a single dose of Sputnik V can significantly increase the antibody level in vaccine recipients without a history of COVID-19 (10). Also, the induction of memory B cell responses in Sputnik V was promising (12). Regardless of the high efficacy of the Sputnik V against the wild-type SARS-CoV-2 and the alpha variant (VOC 1, B.1.1.7), there are some concerns about the efficacy of the vaccine in dealing with the emerged variants, such as beta or B.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of circulating binding and neutralizing antibodies are highly variable between individuals, but in most patients, humoral response decays over the first 6-8 months post-infection (Dan et al, 2021;Sherina et al, 2021, Wheatley et al 2021. It has been shown that SARS-CoV-2-specific memory B cells (Sherina et al, 2021;Byazrova et al, 2021a;Byazrova et al, 2021b;Sokal et al, 2021;Marcote et al, 2021) and T cells are maintained in COVID-19 convalescent patients at least for 6-8 months (Dan et al, 2021;Sherina et al, 2021;Zuo et al, 2020;Bilich et al, 2021), and the latest reports further extend this margin to up to 10-15 months (Jung et al, 2021, Marcote et al, 2021. Although the numbers of circulating T cells decrease over time (Wheatley et al, 2021;Marcotte et al, 2021), these cells retain the ability to secrete cytokines (Kang et al, 2021) and to expand (Rodda et al, 2021) upon re-stimulation with the appropriate antigen.…”
Section: Introductionmentioning
confidence: 99%